Multilingualism from Manuscript to 3D Intersections of Modalities from Medieval to Modern Times - Włodarczyk, Matylda; Tyrkkö, Jukka; Adamczyk, Elżbieta (Routledge Studies in Multimodality, 2023)
modalities; modalities of communication; multilingual communication; historical communication; multimodal resources; multimodality; semiotic resources